1 & 2 Samuel - Firth, David G (Nottingham, England : Apollos ; Downers Grove : InterVarsity, 2009)
The books of Samuel contain two of the Bible's best known stories--David's encounter with Goliath and his sin with Bathsheba and the murder of Uriah. However, the text does more than just tell stories, particularly of how first Saul and then David became king of Israel and the mistakes both made; it also offers a profoundly theological reflection on this formative part of Israel's history and an artistic telling of it. We are told how Israel's monarchy began: the way this is done points to the interpretation of these events. Thus, in this commentary, David G. Firth takes seriously the narrative techniques employed in and 2 Samuel. Arguing that the books are a carefully constructed, intentional unit for interpretation, he explores the central theme of how the reign of God is worked out in the interplay between king and prophet. --From publisher's description
Includes bibliographical reference (pages 551-577) and indexes
Keywords: Bible. -- Commentaries